Skrining dan Edukasi Gangguan Pendengaran Pada Anak Sekolah - Martini, Endang; Probandari, Ari; Pratiwi, Dewi; Universitas Sebelas Maret Surakarta, Sumardiyono - (IJMS - Indonesian Journal on Medical Science, 2017)
Abstract: Hearing problems among children should be detected early because it will influence childâs speech ability development. Unlike the other disability, hearing disability in children is not clearly visible. Hearing disabilities in children can cause problems in language learning that then lead to disorders of social ability and emotional disorders. The purpose of this study was to describe the results of the examination of ear function among school children and to educate healthy behaviors in children. The research method used a descriptive observational study. Data of hearing loss was obtained by interviews. The screening of hearing lost was performed by Ear-Nose-Throat specialists. The subjects were elementary school children grade 1 in a public elementary school at Surakarta. The findings showed 80% of the students always perform diligent ear cleaning, 80% of them used cotton bud for ear cleaning, and 88% perceived none ear disorders. About 24% and 79% of the students had ear cerumen probe in the private and public elementary school respectively. The overall screening cerumen found in the ear canal by 33% of the total number of children examined. For education, the children followed a coloring contest image